2015
DOI: 10.1097/md.0000000000001582
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of Changes in Activation Among Facial Nerve Injury

Abstract: Patients suffering different intervals of facial nerve injury were investigated by functional magnetic resonance imaging to study changes in activation within cortex.Forty-five patients were divided into 3 groups based on intervals of facial nerve injury. Another 16 age and sex-matched healthy participants were included as a control group. Patients and healthy participants underwent task functional magnetic resonance imaging (eye blinking and lip pursing) examination.Functional reorganization after facial nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 32 publications
(41 reference statements)
1
24
0
Order By: Relevance
“…These results indicate that treatment time after injury is also an important variable affecting stem cell transplantation in the treatment of SCI. The reason may be that the nervous functional reorganization after injury is time-dependent 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that treatment time after injury is also an important variable affecting stem cell transplantation in the treatment of SCI. The reason may be that the nervous functional reorganization after injury is time-dependent 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of nerve function depends on the recovery of axonal stretch injury, strengthening of remaining motor synapses at the neuromuscular junction, and even cortical reorganization and sensorimotor reintegration processes. 16,25,26 It is accepted that the best recovery of facial nerve function for a postoperative facial nerve palsy occurs within the first 6 to 12 months, 18,22,25 and after 1 year, nerve grafting techniques should be considered to offer patients with residual dysfunction the best chance of recovery. Notably, current electrophysiological monitoring capabilities fail to predict which patients will be left with "poor" facial function after surgery (House-Brackmann grade IVor worse), which prohibits the use of these tools for intraoperative decision-making regarding neural grafting techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal lobe and insula were also suggested to play an important role in sensorimotor function as an ipsilateral pathway ( Kobayashi et al, 2003 ). Overactivation in motor cortices in patients with FN injury has been sufficiently substantiated ( Calistri et al, 2020 , Xiao et al, 2015 ). When performing facial motor tasks, patients must pay more attention to facial movements and use more facial motor imagery than healthy people.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that neurons in CNS initially controlling the transferred nerve can be reeducated to assume new functions after ectopic neurorrhaphy ( Molina-Rueda et al, 2019 ). In previous studies using blood oxygen level-dependent functional magnetic resonance imaging (fMRI), we found changes with time in the activation of facial movement related areas of patients after FN injury ( Xiao et al, 2015 ). The study performed by Rottler et al shows that hypoglossal-facial transfer resulted in an outcome-dependent cortical reorganization with activation of the cortical tongue area for restituted movement of the lip ( Rottler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%